Pengaruh Penggunaan Aplikasi Agronow dan Motivasi Kerja Terhadap Disiplin Kerja Karyawan dalam Mengikuti Pelatihan Karyawan sebagai Variabel Intervening pada PTPN IV Regional I Medan - Rifyan Helmy S; Ihsan Effendi; Indawati Lestari (Program Studi Agribisnis Fakultas Pertanian, 2026)
This study is based on the importance of applying digital technologyto support work effectiveness and increase employee motivationin order to create high discipline in the work environment. This quantitative research was conducted using the SmartPLS 4.1.1.4 application. The research population consisted of 85 employeesof PTPN IV Regional I Medan. The results showed that theuse of the Agronow application and work motivation had a positive andsignificant effect on employee training. Employee training had a positiveand significant effect on employee work discipline. In addition, the use ofthe Agronow application and work motivation has a positive and significant influenceon employee work discipline with a T-Statistics value of 2.678 >1.96 and P-Values of 0.004 < 0.05, T-Statistics of 2.991 > 1.96and P-Values of 0.003 < 0.05. Employee training plays a significant rolein mediating the effect of Agronow Application usage and work motivation onemployee work discipline with a T-Statistics value of 2.695 > 1.96 andP-Values of 0.022 < 0.05, T-Statistics of 2.895 > 1.96 andP-values of 0.016 < 0.05. Thus, the effective implementation of the Agronow application, supported by high work motivation and continuous employee training, can improve employee work discipline at PTPN IVRegional I Medan.